2011
DOI: 10.1371/journal.pone.0024363
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Hemoglobin Expression by Oxidative Stress in Hepatocytes and Its Implication in Nonalcoholic Steatohepatitis

Abstract: Recent studies revealed that hemoglobin is expressed in some non-erythrocytes and it suppresses oxidative stress when overexpressed. Oxidative stress plays a critical role in the pathogenesis of non-alcoholic steatohepatitis (NASH). This study was designed to investigate whether hemoglobin is expressed in hepatocytes and how it is related to oxidative stress in NASH patients. Analysis of microarray gene expression data revealed a significant increase in the expression of hemoglobin alpha (HBA1) and beta (HBB) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
112
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 44 publications
7
112
0
Order By: Relevance
“…As expected, markers of oxidative stress are detectable in ob/ob hepatocytes both in vivo and in vitro: accumulation of ROS, a high abundance of glutathione peroxidase-3 (GPX3) (reflecting the adaptive activation of antioxidant defenses), and a high abundance of hemoglobin α (HBA1) recently correlated with oxidative stress in patients with NASH (ref. 65 and Supplemental Figure 6, A-C). We treated primary ob/ob hepatocytes with the antioxidant NAC and examined cell cycle progression.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, markers of oxidative stress are detectable in ob/ob hepatocytes both in vivo and in vitro: accumulation of ROS, a high abundance of glutathione peroxidase-3 (GPX3) (reflecting the adaptive activation of antioxidant defenses), and a high abundance of hemoglobin α (HBA1) recently correlated with oxidative stress in patients with NASH (ref. 65 and Supplemental Figure 6, A-C). We treated primary ob/ob hepatocytes with the antioxidant NAC and examined cell cycle progression.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, hypoxia upregulates hemoglobin expression in alveolar epithelial cells in vitro (22) and bacterial lipopolysaccharide upregulates the β hemoglobin subunit in murine macrophages (23). H 2 O 2 increases Hb-α1 and Hb-β expression in HepG2 and HEK293 cells, which, in turn, protects the cells from oxidative stress (24). Hemoglobin has been localized in kidney mesangial cells, where it confers oxidative stress resistance (25).…”
Section: Discussionmentioning
confidence: 99%
“…; n = 3; *p < 0.05; **p < 0.01. stress, the rate of the gaseous transmitters produced, as well as many additional factors. Based on several sets of independent investigations, it appears that when oxidative stress is relatively low, hemoglobin (and its degradation products, for example, heme) increases oxidative stress, and scavenges physiologically necessary amounts of NO, but when the degree of oxidative stress is high, hemoglobin tends to protect from cellular damage (22)(23)(24)(25)(26)(27)31). One also has to keep in mind that hemoglobin decomposes into multiple products, including heme (which increases oxidative stress, but also acts as a substrate of the gasotransmitter carbon monoxide, produced by heme oxygenase), while other degradation products (for example, bilirubin) have significant antioxidant effects (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our study showed involvement of other factors which have also been proposed as indices of oxidant stress status, namely serum hemoglobin levels were significantly and independently associated with GGT activity (inversely) and albumin concentration (positively), while OC correlated with bilirubin level. Hemoglobin [116,117], albumin [118][119][120] and bilirubin [118,121] exhibit potent antioxidant properties. Increases in GGT activity may reflect the responses of counteracting mechanisms to protect against oxidative damage.…”
Section: Potential Mechanisms: Combining Regulatory Elementsmentioning
confidence: 99%